Size selection of liquid-exfoliated 2D nanosheets - Ogilvie, Sean P.; Large, Matthew J.; O'Mara, Marcus A.; Lynch, Peter J.; Lee, Cheuk Long; King, Alice A. K.; Backes, Claudia; Dalton, Alan B. (2D Materials, 2019)
Here we present a size selection model for liquid-exfoliated 2D nanosheets. The ability to consistently select exfoliated nanosheets with desired properties is important for development of applications in all areas. The model presented facilitates determination of centrifugation parameters for production of dispersions with controlled size and thickness for different materials, solvents and exfoliation processes. Importantly, after accounting for the influence of viscosity on exfoliation, comparisons of different solvents are shown to be well described by the surface tension and Hansen parameter matching. This suggests that previous analyses may have overestimated the relative performance of more viscous solvents. This understanding can be extended to develop a model based on the force balance of nanosheets falling under viscous drag during centrifugation. By considering the microscopic aspect ratio relationships, this model can be both calibrated for size selection of nanosheets and compare the exfoliation processes themselves.